Domestication of Asian Redtail Catfish (Hemibagrus sp.) as an Effort to Preserve Local Fish at the Loka Ngrajek in Magelang, Central Java - Eny Heriyati; Toni Kuswoyo; Shima Bhaskara Ayuningrum; Anshar Haryasakti (Universitas Muhammadiyah Palembang, 2023)
The Baung fish (Hemibagrus sp.) were used in this research were the first domesticated breed of native fish from Elo river, Magelang, Central Java. The growth pattern of Baung fish is very important to know for management and spesies conservation. The aim of this research were to analyze the size distribution, growth patterns and condition factors of Baung fish as a basis for managing fish resources. The research was conducted in September 2023 at Loka Ngrajek Magelang, Central Java. The fish samples used were the result of first generation domestication which were cultived in concrete tanks for six months. The body weight of Baung fish ranged from 66 g to 330 g. The survival rate of Baung fish from 5-7 cm to 20-35 cm were 55 ± 2.7%, while when enlargement it reached 93 ± 3.6%. Loka Ngrajek succeeded in domestication and produced the first generation with daily fish growth of 2.65 ± 0.11%. Cultivated fish have a length-weight relationship model W = 0.0104X2.9414, which showed negative allometric meaning that the increase in length was faster than the increase in weight.